Differential Atrophy in the Hippocampal Subfield Volumes in Four Types of Mild Dementia - Huang, Lin; Chen, Keliang; Hu, Xiaochen; Guo, Qihao (Frontiers in Neuroscience, 2020)
Objectives To investigate the bilateral hippocampal subfield volumetric differences in four types of mild dementia, namely typical Alzheimer’s disease (tAD), dementia with Lewy bodies (DLB), semantic dementia (SD), and posterior cortical atrophy (PCA), to assist differential diagnosis. Methods One hundred three participants, including 22 tAD, 34 SD (17 left SD and 17 right SD), 15 DLB, 12 PCA patients, and 20 normal controls (NC), were recruited. All subjects received standard neuropsychological assessments and magnetic resonance imaging (MRI). The hippocampal subfields were automatically segmented via Freesurfer. The study compared the volumetric differences and used the receiver operating characteristic (ROC) curves to estimate the efficacy of each hippocampal subfield to distinguish between groups. Spearman correlation analysis was used to investigate the relationship between memory recall scores and hippocampal subfield volumes. Results The hippocampal subfield atrophy varied in different groups: tAD, SD, and PCA patients had subregional atrophy in bilateral hippocampi compared to NC, and DLB patients showed preserved volumes; left SD patients suffered the most severe atrophy of the left hippocampus, and right SD patients were atrophied mostly in the right hippocampus. There was no significant difference in the volume of hippocampal subregions between tAD and PCA subjects, but the former tended to be atrophied more asymmetrically. ROC analysis showed that, for discrimination, the areas under the curve (AUC) of some subfields were larger than the total hippocampus, but none observed significant difference. In addition, immediate recall scores were correlated to left CA1, CA2/3, CA4/DG, subiculum, and presubiculum (p < 0.05), and delayed recall scores were strongly related to bilateral CA2/3, CA4/DG, subiculum, and presubiculum (r = 0.38–0.52, p < 0.05). Conclusion Differential atrophy patterns in the bilateral hippocampal subfield volumes could serve the differential diagnosis in patients with different causes of mild dementia: left CA1 for tAD; left presubiculum for LSD; right CA4/DG, right presubiculum, and right subiculum for RSD; CA4/DG and right CA2/3 for DLB; right CA2/3 and right CA4/DG for PCA. Additionally, several hippocampal subfield volumes were significantly associated with memory scores, further highlighting the essential role of the hippocampus in memory decline.